Preeclampsia/Eclampsia candidate genes show altered methylation in maternal leukocytes of preeclamptic women at the time of delivery. (2nd July 2016) - White, Wendy M.; Sun, Zhifu; Borowski, Kristi S.; Brost, Brian C.; Davies, Norman P.; Rose, Carl H.; Garovic, Vesna D.
ABSTRACT: Objective : To analyze methylation profiles of known preeclampsia/eclampsia (PE) candidate genes in normal (NL) and preeclamptic (PE) women at delivery. Methods : A matched case–control study comparing methylation in 79 CpG sites/33 genes from an independent gene set in maternal leukocyte DNA in PE and NL ( n = 14 each) on an Illumina BeadChip platform. Replication performed on second cohort (PE = 12; NL = 32). Results : PE demonstrates differential methylation in POMC, AGT, CALCA, and DDAH1 compared with NL. Conclusion : Differential methylation in four genes associated with PE may represent a potential biomarker or an epigenetic pathophysiologic mechanism altering gene transcription.